Nano-Bacillus amyloliquefaciens as a dietary intervention in nile tilapia (Oreochromis niloticus): Effects on resistance to Aeromonas hydrophila challenge, immune-antioxidant responses, digestive/absorptive capacity, and growth - Mohammed E. Hassanin; Abdelhakeem El-Murr; Amr R. EL-Khattib; Abdelwahab A. Abdelwarith; Elsayed M. Younis; Mohamed M.M. Metwally; Sameh H. Ismail; Simon J. Davies; Afaf N. Abdel Rahman; Rowida E. Ibrahim (Heliyon)
The present investigation proposed an innovative trial at the probable beneficial effects of nano-Bacillus amyloliquefaciens (NBA) dietary incorporation on the Nile tilapia (Oreochromis niloticus). The investigation included the impact on the growth, digestive functions, immune-antioxidant indices, and resistance to Aeromonas hydrophila challenge. A total of 135 fish (35.14 ± 0.12 g) were equally allocated into three groups (45 fish/group; 15 fish/replicate) in triplicates for 70 days. The control, NBA2, and NBA4 groups were fed basal diets enriched with 0, 102, and 104 CFU/kg NBA, respectively. Following the feeding experiment, all experimental groups were injected with 0.1 mL (1.5 × 106) A. hydrophila, and the fish mortalities were observed for 14 days. The outcomes showed that dietary NBA (NBA4 followed by the NBA2 diet) augmented the growth variables (final body weight, total weight gain, and specific growth rate) and condition factor and declined the feed conversion ratio. The intestinal digestive enzyme (amylase and lipase) and growth hormone levels were increased and the serum glucose level was decreased by dietary NBA. Furthermore, NBA diets enhanced the immune (total protein, globulin, lysozyme, complement 3, myeloperoxidase, and phagocytic activity) and antioxidant (superoxide dismutase, catalase, and total antioxidant capacity) parameters. The intestinal histology revealed no pathological lesions with a significant improvement in the intestinal histomorpho-measures (villus height and width, villus surface area, lamina propria thickness, and tunica muscularis thickness) by NBA diets in a dose-dependent manner. In the fish intestine, the B. amyloliquefaciens count was increased in the NBA groups (NBA4 group followed by NBA2 group) with no discernible difference in the total bacterial count. Fish resistance to the A. hydrophila challenge was increased by increasing the survival % in the NBA4 group (91.70 %) followed by the NBA2 group (83.30 %) compared to the control group (70.80 %). Overall, dietary NBA (especially 104 CFU/kg diet) could be a promising feed supplement in the Nile tilapia diets for improving their growth, health, and resistance to bacterial challenges.